HUBUNGAN STATUS GIZI DENGAN DISMENORE PADA REMAJA PUTRI - Alex Brando Silalahi; Ari Pristiana Dewi; Juniar Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
One of the elements which play a role in realizing reproductive health in adolescents is nutritional status. TheAbnormal nutritional status will influence the growth and reproductive function that will affect menstrual disordersincluding dysmenorrhea. This study aimed to find out the relationship between nutritional status and dysmenorrhea infemale adolescents in SMA Negeri 8 Pekanbaru. This research used descriptive correlational research design withcross-sectional approach. The sample of the study was 215 respondents taken based on inclusion criteria usingconsecutive sampling technique. The instruments used were questionnaires, weight scales, and microtoise. The analysesused were univariate analysis to know the frequency distribution and bivariate analysis using chi-square test. Theresults showed that from 189 respondents (87.9%) who had normal category nutritional status, there were 13respondents (6.9%) experienced severe pain. Whereas, from 26 respondents (12.1%) who were categorized to have overnutritional status (fat and obesity), there were 7 respondents (26,9%) experiencing severe pain. The results of statisticaltest obtained p-value 0.004 < alpha (0,05), therefore it can be concluded that there is a relationship between nutritionalstatus and dysmenorrhea in female adolescents in SMA Negeri 8 Pekanbaru. Researcher recommends that femaleadolescents improve and maintain normal nutritional status by losing weight for obese adolescents and switch to ahealthier body mass index range.Keywords : Adolescents girls, dysmenorrhea nutritional status